O ensino e a aprendizagem na sala de aula numa perspectiva dialética - de Almeida, José Luis Vieira [UNESP]; Grubisich, Teresa Maria (My University, 2011)
In this paper it is argued, the dialectical mediation focus, the relation between teaching and learning and their effects in the classroom. This essay aims to contribute to some misconceptions about this relation are resolved and for teachers to better understand what teaching is, what learning is, what kind of relation exists between both of them and what the teacher role is about these processes, which involve philosophical bases that should be known and understood by teachers.
The teaching and the learning in the classroon on a dialetic perspective
Keywords: Classroom; Dialectical; Learning; Mediation; Teaching